Electronic Students Worksheet on Linear Equations and Inequalities - Soffi Widyanesti Priwantoro; Ayu Virdasari; FAHMI, SYARIFUL (Pusat Studi Pengembangan Pembelajaran Matematika, 2022)
The Purpose of this research is to develop an electronic student worksheet based on android in linear equation and inequalities. Method of this research using ADDIE model, there are five steps, namely Analysis, Design, Dedvelopment, Implementation and Evaluation. This research use experts of content and media while the subject are students in Mts N 1 Tanggamus. Meanwhile the research instrument are interview and questionnaire. Based on calculation, the electronic students worksheet reached 3.90 in good criteria for content expert and 4.28 in very good criteria for media expert. It shows that the electronic student worksheet is valid and its also practical based on small class trial which reach 4.93 in very good criteria and also for large class trial reach 4.75 in very good criteria.